Management of milkfish broodstock. - Emata (Tigbauan, Iloilo, Philippines SEAFDEC, 1992., 1992)
Aquaculture Extension Manual No. 20
Keywords: Seed production; Reproduction; Milkfish culture; Spawning; Manuals; Brood stocks